2018
DOI: 10.1002/acr.23410
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Incident Chronic Obstructive Pulmonary Disease in Rheumatoid Arthritis: A Population‐Based Cohort Study

Abstract: In our population-based cohort, individuals with RA had a 47% greater risk of COPD hospitalization compared to the general population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 41 publications
4
27
0
1
Order By: Relevance
“…Diagnosis of COPD in RA patients may often be delayed due to subtle and non-specific early symptoms, which may be further masked due to restricted mobility from joint disease. The finding of our study is in line with the conclusion by some prior studies [27]. …”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Diagnosis of COPD in RA patients may often be delayed due to subtle and non-specific early symptoms, which may be further masked due to restricted mobility from joint disease. The finding of our study is in line with the conclusion by some prior studies [27]. …”
Section: Discussionsupporting
confidence: 94%
“…There is a growing body of literature suggesting that rheumatoid arthritis (RA) is associated with an increased risk of incident COPD compared to matched general population. Studies have been carried out in various regions of the world- Canada, Israel, Taiwan, Netherlands, Sweden and Minnesota, all suggesting that COPD is more prevalent in RA [27]. Although smoking is known to be a major risk factor for development and progression of COPD, the presence of substantial number of COPD patients who have never smoked suggests that other factors may play a role, with inflammatory and immune responses being important ones [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Several independent reports have demonstrated linkages between RA and COPD prevalance ( McGuire et al, 2017 ; Bieber et al, 2013 ; Shen et al, 2014 ) and RA and COPD hospitalization ( McGuire et al, 2017 ; Shen et al, 2014 ). There findings argue strongly for common shared, automimmue pathways ( Zhang et al, 2014 ; Feghali-Bostwick et al, 2008 ; Packard et al, 2013 ) that may activate protein citrullination ( Rocha-Muñoz et al, 2015 ; Makrygiannakis et al, 2008 ; Rangel-Moreno et al, 2006 ; Scally et al, 2013 ), oxidative stresses ( Vuorinen et al, 2008 ; Volonte et al, 2009 ), and matrix remodeling ( Zandvoort et al, 2008 ) all of which have been implicated in the etiology of both emphysema and fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Smoking has been implicated in the development ( Kelly et al, 2014 ; Saag et al, 1996 ; Gochuico et al, 2008 ) and coarsening of ILD ( Antoniou et al, 2013 ) and is associated with the presence of emphysema on CT at lower pack-year ranges than that seen in chronic obstructive pulmonary disease (COPD) controls ( Antoniou et al, 2013 ). A recent large Canadian study demonstrated that RA patients have a 47% adjusted higher risk of hospitalization for COPD than the general population, with results maintained following modelling for potential confounding effects of smoking ( McGuire et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…A recent British study following 24,625 patients with RA, for over 10 years, found that those with RA had a 47% higher risk of COPD than a non-RA patient group. 5 Another meta-analysis of four studies showed that RA patients indeed had a greater risk of COPD than did non-RA patients, with a pooled risk of 1.99 (95% Confidence Interval [CI]: 1.61-2.45). 6 Furthermore, a study revealed that patients with RA, suffering from concomitant COPD, had double the likelihood of mortality of those with RA only.…”
Section: Introductionmentioning
confidence: 99%